Elaboração e aplicação de descritores moleculares, morfológicos e físico-químicos para caracterização de germoplasma de Mangabeira - Vitória, Marina Ferreira da (2017)
Trees native to Brazil, mangaba (Hancornia speciosa Gomes) is a species mainly extractive, occurrence in various regions of the country. The Northeast holds of 99% of all production, being the Sergipe state the largest producer. The potential for the use of the pulp is quite varied, is used for fresh consumption and industrialization of various foods and drinks. The species has been threatened with extinction by several factors that are contributing to reduction of their naturally occurring areas. To enlarge the database for the use and knowledge of the variability of this species, as well as support to its domestication, it is necessary to carry out studies and characterization of genetic diversity. The present work was developed with the purpose to display and evaluate morphological descriptors, physico-chemical and molecular in germplasm of mangaba. The genebank of mangaba (BGmangaba) of Embrapa Coastal Tablelands was implemented in 2006 and has 213 individuals, representing 22 accessions. For morphological and physico-chemical characterization, 21 descriptors were used on 54 plants, from 10 access on fruit-bearing stage. There was wide variation and significance among and with access, without direct relationship with its origins. Fourteen descriptors were considered of significant importance for studies of characterization of mangaba, without loss of information on characterization. The accesses that presented the most significant values were AB, BI, CA, LG, TC, with greater development when compared to the others, the accesses TC, AB, AD, stand out as attractive, due to their physicochemical characteristics and the accesses BI and TC with fruits of larger masses, characteristic of interest for the in natura consumption and agroindustrial processing. All accesses of the BAG were used for molecular characterization and genetic structure, using nine microsatellite markers (SSR). 100% of polymorphism was observed with the use of SSR. 147 alleles were identified, with an average of 16 alleles for loco. Reliability was verified with stress values (0.042) and correlation (0.988). The alleles showed high frequency of heterozygosity (Ho>Ho). Fst values (0.22) and f (0.07) indicated moderate population structure, being presented greater diversity within the traffic. Bayesian analysis indicated a group with k=2, confirmed with the UPGMA. Were formed two distinct groups, grouped according to similarity. The pairs of individuals PM5 and GX2; CN1 and CN9; G18 and PA1; JA14 and JA15; OI8 and OI9, all belonging to the G2 were those closest genetically. The combination of the keywords used in this study, favors the identification of different individuals and with features of interest. The germplasm evaluated has diversity among and within access.The results will collaborate in the conservation of this material strategies and future breeding programs. The proposed descriptors will be used by FAO/Biodiversity.